Zatrudnienie absolwentów studiów bibliologicznych w łódzkich bibliotekach w latach 2006-2010 - Sójkowska, Iwona; Podgórski, Filip (Acta Universitatis Lodziensis. Folia Librorum, 2013)
The survey was held in the middle of 2011 which aimed to establish the existing employment policy in Lodz academic and public libraries. The authors attempted to examine the actual state of employment and personnel policy in the libraries during last five years. The essential issue in the survey were factors which constituted the candidate’s appeal for the employer, as it would be important information for students in their education as well as professional development.